Queen Elizabeth II an oral history - Strober, Deborah H. 1940-; Strober, Gerald S. 1935- (Pegasus Books, 2022)
"There seems an unquenchable fascination with the British royal family on both sides of the Atlantic, borne out by the popularity of The Crown on Netflix, the spotlight on the Sussexes and Cambridges, and the media attention on the death of Prince Philip. These detailed interviews and insightful accounts range from the very early years of her reign to Prince Phillip's death in 2021. Covering the shocking death of her father and the adjustment required of a newly married couple as well as the turmoil of the later years and her grandchildren's families. This lavishly produced hardback with rarely seen color photos paints a full, detailed and sympathetic portrait of a life lived in service. Featuring interviews from diverse sources from private staff at Buckingham Palace and family friends, to international figures like Nelson Mandela, it contains a broad spectrum of views on Queen Elizabeth II--her story and her personality and how her life has intersected and impacted others."--Amazon.com